What factors affect school attendance? Quantitative and qualitative study of evidence from Nepal - Bhattarai, Niroj Kumar, author; Bernasek, Alexandra, advisor; Pena, Anita Alves, advisor; Vasudevan, Ramaa, committee member; Kent, Suzanne, committee member; Canetto, Silvia, committee member (Colorado State University. Libraries, 2017)
There exist many factors that impact school attendance of students in developing countries. Factors range from the distance to school from a student's home to the availability of gender-specific restrooms. A project in the south east part of Nepal that built gender-specific restrooms and brought running water to the school increased enrollment and attendance of the students, particularly of girls. To study what other factors impact attendance, a survey was conducted in and around Kathmandu Valley, Nepal. An econometric study of the data generated by the survey showed that time spent studying at home, having an educated mother and an employed mother, all had positive effect on students' attendance. Distance to school, presence of siblings, and lack of computers had negative effects on attendance. The data also demonstrated gender differences in what and how various factors affected attendance at the secondary level of education in Nepal.
Keywords: development economics; menstrual; school attendance; gender; attendance; Nepal